An Evaluation of the Design Parameters of a Variable Bearing Profile Considering Journal Perturbation in Rotor–Bearing Systems - Adawiya Ali Hamzah; Abbas Fadhil Abbas; M. N. Mohammed; H. S. S. Aljibori; Hazim U. Jamali; Oday I. Abdullah (Designs, 2023)
A variety of bearing profile designs can be used to improve the performance of a rotor–bearing system in severe conditions, such as operating with a shaft misalignment. Misalignments usually occur due to a deformation of the journal, bearing wear, and installation errors. This paper investigates the effects of bearing design parameters under a 3D journal misalignment for a wide range of length-to-diameter ratios to consider short, finite-length, and long journal bearings. Furthermore, the dynamic response of the system to journal perturbation considering linear and parabolic bearing profiles is also investigated. A numerical solution is identified based on the finite difference method, and the equations of motion are derived based on a linear stability analysis in which the fourth-order Runge–Kutta method is used to obtain the journal trajectories. The results show that both profiles help to enhance the rotor–bearing system’s performance regarding the lubricant layer thickness and pressure distribution, in addition to the shaft critical speed over the entire considered range of length-to-diameter ratios. This enhancement reduces the misalignment negative effects on the system performance. The response of the rotor-bearing system to journal perturbation in the case of the parabolic profile are very close to the perfect alignment case in comparison with a linear modification.